Epothilones – a new class of microtubule-targeting agents in the treatment of breast cancer - Wysocki, Piotr J. (Contemporary Oncology/Współczesna Onkologia, 2008)
Resistance of tumour to chemotherapeutic agents ultimately leads to treatment failure in the majority of breast cancer patients. There is a continuous search for novel methods preventing development of tumour chemoresistance and for new drugs with cytotoxic potential in breast cancer. In 1996 a new class of microtubule-targeting agents – epothilones – was described by Reichenbach et al. Epothilones are microtubule inhibitors with low susceptibility to several mechanisms of drug resistance. Among 350 synthetic epothilone analogues, several have been tested in patients with various malignancies in phase I and II clinical trials. In phase I/II clinical studies in breast cancer patients, ixabepilone, patupilone, sagopilone, KOS-862 and BMS-310705 have been demonstrated to induce clinical responses at acceptable toxicity. The toxicity profile of epothilones is similar to taxanes (myelosuppression, neuropathy); however, epothilones do not induce hypersensitivity reactions requiring a corticosteroid-based premedication. So far only the results of one clinical phase III trial evaluating epothilones in breast cancer patients have been published. In the study, combination of ixabepilone and capecitabine was superior to capecitabine alone in terms of clinical responses and progression-free survival in breast cancer patients previously treated with anthracyclines and taxanes. In October 2007, the FDA approved ixabepilone for use in patients with metastatic or locally advanced breast cancer who have not responded to anthracyclines and taxanes.